Law of cosines

From Math Images

Revision as of 16:13, 2 June 2011 by Rscott3 (Talk | contribs)
Jump to: navigation, search
Image:inprogress.png

Law of Cosines

The law of cosines is a trigonometric extension of the Pythagorean Theorem.


Contents

Basic Description

The law of cosines is a formula that helps in triangulation when two or three side lengths of a triangle are known. The formula relates all three side lengths of a triangle to the cosine of a

particular angle.

 c^{2} = a^{2} + b^{2} - 2ab \cos C

When to use it: SAS, SSS.

A More Mathematical Explanation

Proof

Let  \vartriangle ABC be oriented so that UNIQ4d52942f4634f841-mat [...]

Proof

Let  \vartriangle ABC be oriented so that  C is at the origin, and  B is at the point (a,0).

Image:Law_of_cosines_proof.jpg

Distance Formula

 distance = \sqrt {(x_{2}-x_{1})^{2} + (y_{2}-y_{1})^{2}}

c is the distance from  A to  B.

Substituting the appropriate points into the distance formula gives us

 c = \sqrt {(a-b \cos C)^{2} + (0-b \sin C)^{2}}

Squaring the inner terms, we have

 c = \sqrt {(a^{2}-2ab \cos C+b^{2} \cos^{2} C) + (b^{2} \sin^{2} C)}

Since  \cos^{2} C +  \sin^{2} C = 1,

 c = \sqrt {(a^{2}+b^{2}-2ab \cos C+b^{2}}

Square both sides for

 c^{2} = (a^{2}+b^{2}-2ab \cos C+b^{2}

Example Triangulation

Complete the triangle using the law of cosines.


 c^{2} = a^{2} + b^{2} - 2ab \cos C

Image:SAS triangle.jpg

Solution

To find the side length c,


 c^{2} = 6^{2} + (6 \sqrt{2})^{2} -2 (6) (6 \sqrt{2}) \cos 45^\circ

Simplify for

 c^{2} =36 + 36 (2) - 72 \sqrt{2}) \cos 45^\circ

Since  \cos 45^\circ = \frac{1}{\sqrt{2}}, substitution gives us

 c^{2} =36 + 36 (2) - 72 \sqrt{2} (\frac{1}{\sqrt{2}})

Simplify for

 c^{2} =36 + 72 - 72


 c^{2} =36

Taking the square root of both sides gives us

 c =6


Now we can orient the triangle differently to get get a new version of the law of cosines so we can find angle measure B,


 b^{2} = a^{2} + c^{2} - 2ab \cos B

Substituting in the appropriate side lengths gives us

 (6 \sqrt{2})^{2} = 6^{2} + 6^{2} - 2(6)(6) \cos B

Simplify for

 36 (2) = 36 + 36 - 72 \cos B

72 = 72 - 72 \cos B

Subtracting 72 from both sides gives us

0 = - 72 \cos B

Dividing both sides by -72 gives us

0 = \cos B

Using inverse trigonometry, we know that

B = 90^\circ

And we can find the last angle measure A by subtracting the other two measures from  180^\circ

 180^\circ - 90^\circ - 45^\circ = 45^\circ

 A=45^\circ

Image:SAS_solution.jpg




Teaching Materials

There are currently no teaching materials for this page. Add teaching materials.









If you are able, please consider adding to or editing this page!

Have questions about the image or the explanations on this page?
Leave a message on the discussion page by clicking the 'discussion' tab at the top of this image page.
[[Category:]]






Personal tools